Beyond arrows in process models: A user study on activity dependences and their rationales. Issue 100 (September 2021) - Adamo, Greta; Di Francescomarino, Chiara; Ghidini, Chiara; Maggi, Fabrizio Maria
Abstract: Despite the number and variety of business process modelling languages and notations available in the Business Process Management field, all of them mainly focus on a single type of relationship holding between business process activities, namely the activity execution order within the control flow. However, other types of relationships may hold between activities (e.g., co-occurrence or causal constraints) and the motivation behind these relationships can also be different (e.g., a norm or an ontological law-of-nature). In this paper, we focus on one type of these activity relationships whose semantics goes beyond the semantics of arrows in traditional business process modelling languages, i.e., on the so called occurrence dependences . In particular, we aim at evaluating whether making these occurrence dependences explicit in business process models could support business process modellers and analysts in their tasks. To this aim, we propose a notation for representing the occurrence dependences and their rationale, and carry out an empirical study with human subjects for evaluating their support in comprehension and redesign tasks; in addition, we qualitatively investigate the effort required for enriching business process models with these dependences. Highlights: Other types of dependences among business process activities that go beyond the activity execution order. A new notation for enriching business process models with activity dependences and their rationales. An empirical evaluation with human subjects on activity dependences and their rationales.